Simulações zootécnicas e análise econômica da criação de cordeiros para abate produzidos com ou sem creep feeding - (:unkn) unknown (Universidade Federal do Pampa, 2012)
The sheep had a new marketing approach from the production of young lambs to the slaughter, making it an excellent alternative to reach the most demanding markets. The aim of this study was to evaluate the profitability of a production system of lambs with the use of creep feeding, varying the rates of pregnancy and days for the slaughter, through simulations. To carry out simulations, 150 sheep were used, with pregnancy rates of 80, 85 and 90% and perinatal mortality of 5%. The average weight at birth was of 3,5 kg/animal, with slaughter to 90, 120 and 150 days old, with GMD of 0,330 and 0,270 kg/day, with and without creep feeding, respectively. Were considered the costs of concentrate, silage, vaccines, dewormers and troughs. The lambs were marketed with R$ values 3,00; 3,50 and 4,00 kg/PV. You can check the birth of 90, 102 and 114 lambs, pregnancy rates of 80, 85 and 90%. The animals produced with the creep feeding had higher daily weight gain, causing the animals to reach a good weight for marketing in a short period of time, unlike observed without creep. With the total sale of the lot, by deducting the amounts spent in the production of lambs, can verify higher profitability and remuneration with lots of creep due to heavier animals for sale. The creep feeding animal weight gain benefits, providing greater profitability. The various costs and prices paid by final product will determine the profit system, thus, the zootechnical simulation serves as a support tool for decision making.
Keywords: Ganho de peso; Idade de abate; Modelagem; Ovinos; Age of slaugther; Gain Weight; Modeling; Sheep; CNPQ::CIENCIAS AGRARIAS